2020
DOI: 10.1177/1538574420947228
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Endovascular Treatment of Dysphagia Lusoria: Report of 2 Cases

Abstract: Dysphagia Lusoria is a condition when aberrant right subclavian artery (ARSA) causes esophageal compression. We report 2 cases of Dysphagia Lusoria treated by hybrid endovascular technique which included subclavian to carotid transposition and embolization of origin of ARSA. By using this technique, we avoided the need for thoracotomy. Both patients had complete symptom relief without any surgery related complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Double aortic arches are treated surgically. It consists of a ligation-section of one arch with release of the esophagus and trachea via thoracotomy, or selective embolization via endoscopy [ 9 , 10 ]. Nevertheless, the indication for surgery need not be systematic, but it is definite if esotracheal compression syndrome is severe [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Double aortic arches are treated surgically. It consists of a ligation-section of one arch with release of the esophagus and trachea via thoracotomy, or selective embolization via endoscopy [ 9 , 10 ]. Nevertheless, the indication for surgery need not be systematic, but it is definite if esotracheal compression syndrome is severe [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The only reported postoperative complication is phrenic nerve injury with elevation of the right hemidiaphragm with rapid improvement afterward [ 21 , 22 ]. Another option for the exclusion of the ARSA stump after subclavian transposition or bypass is embolization of the origin of ARSA using coils [ 23 ]. Closing the origin of ARSA with TEVAR is another option, and several authors have reported this strategy [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, minimally invasive alternatives are now more common, including total endovascular or hybrid techniques. 7 …”
mentioning
confidence: 99%